Relationship between adherence to the mediterranean food pattern and food self-efficacy of higher education students in Portugal: A cross-sectional study - Bruna Brabo; António Raposo; Renata Puppin Zandonadi; Eduardo Yoshio Nakano; Zayed D. Alsharari; Thamer Alslamah; Daniela Costa; Wansoo Kim; Leandro Oliveira (PLoS ONE, 2025)
When students begin their academic life, they are subject to psychological, environmental, and economic changes, which may have implications for their dietary habits. This study aims to assess the relationship between adherence to the Mediterranean food pattern (MFP), nutritional status, and food self-efficacy among a sample of higher education students in Portugal. This cross-sectional study was conducted between May and June 2023, through an online questionnaire. A total of 114 students from public and private higher education participated in this study, predominantly female (68.7%) with a median age of 23 (20; 27) years. It was found that higher body mass index (BMI), older age (p > 0.003; r: 0.273), and greater adherence to the MFP were associated with higher food self-efficacy (p > 0.003; r: 0.273). No correlations were found between the other variables. When feeling stressed, students tend to consume more sweets, fast food, and fewer fruits and vegetables. Based on the correlations between BMI, adherence to the MFP, perceived stress, and food self-efficacy, it can be concluded that higher BMI, older age, and greater adherence to the MFP are associated with higher food self-efficacy. These results can be explored for future dietary interventions in this population group.